MICROBIAL AIR POLLUTION IN THE DENTAL CENTER OF A PRIVATE UNIVERSITY - Ada Romero Coasaca; Raúl Castro Yanahida; Mariela Ladera Nieto; d Hillsman Ángeles Zorrilla; Diego Ángeles Romero (Kiru)
Objective: The aim of this study was to evaluate the air microbial contamination before and during dental procedures (for 4 months) in two dental rooms, in the Dental Center of a private university of Lima- Perú. Material and Method: The study was carried out using a passive air sampling; settle plate, to identify potential infectious microorganisms. The samples were collected in five moments during the period from August to November in the 2017 year, outcomes were expressed in CFU/plate/hour and the Index of Microbial Air contamination (IMA) level was established. Results: In decreasing order it was found: S. negative mannitol (15.9 ± 12.9); yeast fungi (10.3 ± 8.2); S. aureus (9.1 ± 5.9); mold type fungi (1.6 ± 3.1) and enterobacteria (1.2 ± 1.3). Both dental rooms showed regular contamination estimated starting of the average of mesophiles (42.2 ± 22.2). Conclusions: It is necessary to implement methods to reduce the microbial contamination of clinical environments to reduce the risk of crosscontamination